A qualitative study to explore the acceptability and feasibility of implementing person-focused evidence-based pain education concepts in pre-registration physiotherapy training - Thompson, Kate; Milligan, James; Briggs, Michelle; Deane, Janet A.; Johnson, Mark I. (Frontiers in Pain Research, 2023)
Objectives The purpose of this study was to engage with physiotherapy clinicians, academics, physiotherapy students and patients to explore the acceptability, feasibility, and practical considerations of implementing person-focused evidence-based pain education concepts, identified from our previous research, in pre-registration physiotherapy training. Design This qualitative study took a person-focused approach to ground pain education in the perspectives and experiences of people who deliver and use it. Data was collected via focus groups and in-depth semi-structured interviews. Data was analysed using the seven stage Framework approach. Setting Focus groups and interviews were conducted either face to face, via video conferencing or via telephone. This depended on geographical location, participant preference, and towards the end of data collection the limitations on in-person contact due to the Covid-19 pandemic. Participants UK based physiotherapy clinicians, physiotherapy students, academics and patients living with pain were purposively sampled and invited to take part. Results Five focus groups and six semi-structured interviews were conducted with twenty-nine participants. Four key dimensions evolved from the dataset that encapsulate concepts underpinning the acceptability and feasibility of implementing pain education in pre-registration physiotherapy training. These are (1) make pain education authentic to reflect diverse, real patient scenarios, (2) demonstrate the value that pain education adds, (3) be creative by engaging students with content that requires active participation, (4) openly discuss the challenges and embrace scope of practice. Conclusions These key dimensions shift the focus of pain education towards practically engaging content that reflects people experiencing pain from diverse sociocultural backgrounds. This study highlights the need for creativity in curriculum design and the importance of preparing graduates for the challenges that they will face in clinical practice.